METHODOLOGICAL APPROACH FOR ASSESSING THE CYBER RESILIENCE OF INFORMATION AND TELECOMMUNICATION SYSTEMS OF CRITICAL INFRASTRUCTURE OBJECTS UNDER NATIONAL SECURITY THREATS - Shypovskyi, Volodymyr (Ukrainian Information Security Research Journal, 2024)
Since the onset of Russia’s full-scale invasion in February 2022, we have witnessed several innovations in warfare, where unmanned systems in the air, on land, and at sea have transformed approaches to reconnaissance and tactical and operational combat operations. However, the Russo-Ukrainian war has not evolved into a sci-fi battle between automated robotic systems. Nevertheless, information technologies have transformed the nature of war and continue to do so. Military doctrines and combat rules, previously developed, need to be updated to address current and future challenges. The integration of information technologies with armed conflict has not only changed the arsenal of available weapons but also blurred the lines between the physical and cyber domains. Traditional military arsenals, once dominated by tanks, aircraft, and infantry, are now supplemented by powerful cyber capabilities. Modern cyberattack landscapes allow for penetration into the information systems of both military targets and critical state infrastructure, significantly expanding the scope of influence. The rapid development of the cyber domain requires the development of an effective methodological approach to the cyber protection of critical infrastructure objects (CIOs). To enhance the cybersecurity level of these vital objects, analyze current cyber threats, forecast the likelihood of enemy cyberattacks, and implement protection mechanisms for the information and communication systems of CIOs, it is essential to assess the CIOs’ capabilities to maintain functionality under destructive cyber influences and to restore operations after interference with the information and communication systems of CIOs. Developing recommendations for tools to assess cyber resilience will enhance the security and protection level of critical infrastructure under national security threats.